1996
DOI: 10.1063/1.117473
|View full text |Cite
|
Sign up to set email alerts
|

Optical patterning of GaN films

Abstract: Patterned etching of GaN films was achieved with laser-induced thermal decomposition. High-energy laser pulses are used to locally heat the film above 900 °C, causing rapid nitrogen effusion. Excess gallium is then removed by conventional etching. At exposures of 0.4 J/cm2 with 355 nm light, etch rates of 50–70 nm per pulse were obtained. Illumination with an interference grating was used to produce trenches as narrow as 100 nm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
61
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(62 citation statements)
references
References 2 publications
0
61
0
Order By: Relevance
“…[5][6][7] Meanwhile, achieving flexible devices using inorganic films is still very challenging because of the rigidity and brittleness inherent to inorganic films and single-crystalline substrates. [8][9][10][11][12] Nevertheless, high-quality inorganic semiconductors are crucial to achieving better performance and longterm stability of devices. [13][14][15][16] To resolve this problem, growths of inorganic nanostructures and thin films on chemical-vapordeposited (CVD)-graphene have recently been proposed since the inorganic semiconductors prepared on CVD-graphene can be transferred easily to or grown on flexible or elastic substrates to meet the flexibility demand.…”
Section: Doi: 101002/adma201601894mentioning
confidence: 99%
“…[5][6][7] Meanwhile, achieving flexible devices using inorganic films is still very challenging because of the rigidity and brittleness inherent to inorganic films and single-crystalline substrates. [8][9][10][11][12] Nevertheless, high-quality inorganic semiconductors are crucial to achieving better performance and longterm stability of devices. [13][14][15][16] To resolve this problem, growths of inorganic nanostructures and thin films on chemical-vapordeposited (CVD)-graphene have recently been proposed since the inorganic semiconductors prepared on CVD-graphene can be transferred easily to or grown on flexible or elastic substrates to meet the flexibility demand.…”
Section: Doi: 101002/adma201601894mentioning
confidence: 99%
“…Raman scattering spectra were excited in back scattering geometry along [1], with 514.5 nm radiation of an Ar + laser. Figure 3 shows the results of the wafer samples and membranes before and after thermal treatment.…”
Section: Resultsmentioning
confidence: 99%
“…However, the mismatches of thermal expansion coefficient and lattice constant between GaN and Al 2 O 3 , and difficulties in device fabrication due to the poor electrical conductivity of sapphire and low light extraction efficiency have become great obstacles to the high performance of devices. Kelly et al [1] and Wong et al [2,3] reported a laser-based method separating the GaN films from sapphire substrate, but very few papers mentioned the luminescence properties of InGaN/GaN MQWs membranes after laser lift-off, and the changes in photoluminescence spectrum and Raman scattering spectrum of membrane after heat treatmeant have not been ever referred to the extent of our knowledge. In this work, InGaN/GaN MQWs structures were grown on sapphire by MOCVD, and transferred the film onto Si substrates by lift-off technology with KrF pulsed excimer laser.…”
Section: Introductionmentioning
confidence: 96%
“…Thus, GaN can be removed very efficiently via thermal decomposition by methods which enable a controlled local heating of the sample to temperatures above 900 °C. As mentioned above, one possibility to locally decompose GaN is by absorption of intense light with photon energies above the bandgap of GaN (3.42 eV), e.g the 355 nm (3.49 eV) third harmonic of a Nd:YAG pulsed laser [69,70]. The properties of neodymium-doped yttrium aluminum garnet (Nd:YAG) are the most widely studied and best understood of all solid-state laser media.…”
Section: Laser-induced Decomposition Of Ganmentioning
confidence: 99%